Stellarator nonlinearly saturated periodicity-breaking ideal magnetohydrodynamic equilibrium states. (20th September 2018) - Cooper, W.A.; López-Bruna, D.; Ochando, M.A.; Castejón, F.; Graves, J.P.; Kleiner, A.; Lanthaler, S.; Patten, H.; Raghunathan, M.; Faustin, J.M.
Abstract: The relaxation of the constraint of periodicity imposed by the external confining magnetic field coils in a nominally 4-field period Helias advanced stellarator configuration produces weak periodicity-breaking deformations of the plasma. The corrugations are driven by the interaction of the pressure gradient with the magnetic field line curvature and correspond to saturated ideal magnetohydrodynamic interchanges with a mode structure dominated by nonresonant Fourier components. The conditions of quasi-isodynamicity of the Helias reactor system investigated are not significantly altered by the periodicity-breaking distortions.